How does foreign direct investment contribute to sustainable development goals? Evidence from african countries - Aust, Viktoria (2020)
The public and the private sectors play fundamental roles in mobilizing capital to achieve the 2030 Agenda of Sustainable Development. In particular, developing countries can benefit from foreign direct investment (FDI) as a source of external financing in the private sector. This study aims to investigate whether FDI contributes to the achievement of Sustainable Development Goals (SDGs) in Africa. We analyse a sample of 44 African countries regarding their SDG scores and apply a multivariate analysis and an ordered probit model. Our results indicate that the presence of foreign investors positively influences SDG scores. However, although FDI has a positive impact in areas such as basic infrastructure, clean water, sanitation, and renewable energy, some adverse environmental consequences may occur for host countries. In fact, the relationship between FDI and the probability of achieving SDG13 (Climate action) is negative. This study contributes to the literature on sustainable development and can be useful for decision-makers in developing investment plans to support the achievement of SDGs. Furthermore, we provide evidence of a positive influence of FDI on the SDGs, which might encourage further investments in Africa.